2020
DOI: 10.1039/d0gc01240h
|View full text |Cite
|
Sign up to set email alerts
|

Photoreforming of food waste into value-added products over visible-light-absorbing catalysts

Abstract: Food and mixed wastes are converted into H2 and organics over CdS and carbon nitride photocatalysts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
53
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(61 citation statements)
references
References 37 publications
(66 reference statements)
0
53
0
1
Order By: Relevance
“…For example, cereals contain 70-80% carbohydrates (good substrates for PR), 24 whereas meat consists primarily of proteins (10-20%) and fats (2-50%). 25 Proteins are made of long chain(s) of amino acid residues and should undergo PR to a certain extent, 7,26 depending on the quantity of oxidisable functional groups and the complexity of the three-dimensional protein structure. Fats are more challenging to utilise in water-based PR due to their hydrophobicity and (typically) chemically inert hydrocarbon chain.…”
Section: Waste As a Feedstock For Photoreformingmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, cereals contain 70-80% carbohydrates (good substrates for PR), 24 whereas meat consists primarily of proteins (10-20%) and fats (2-50%). 25 Proteins are made of long chain(s) of amino acid residues and should undergo PR to a certain extent, 7,26 depending on the quantity of oxidisable functional groups and the complexity of the three-dimensional protein structure. Fats are more challenging to utilise in water-based PR due to their hydrophobicity and (typically) chemically inert hydrocarbon chain.…”
Section: Waste As a Feedstock For Photoreformingmentioning
confidence: 99%
“…33 Chemical pre-treatment could then be employed to solubilise the sorted waste, thereby facilitating contact between the photocatalyst and substrate during PR and increasing the H2 evolution rate. Several studies have explored this concept and reported enhanced PR following waste hydrolysis and solubilisation under alkaline 7,14,21,22,26,29 or acidic 34,35 conditions, after steam explosion (high-pressure saturated steam) treatment, 36 in metal salt hydrate solutions, 37 or following treatment with enzymes capable of hydrolysing cellulose (cellulases). 35,38,39 Chemical pre-treatment for PR is rarely researched in detail, likely due to a historic focus on PR of simple molecules (e.g.…”
Section: Waste Pre-treatmentmentioning
confidence: 99%
“…The employment of polymers as substrates for photocatalytic transformations has been explored significantly less [29] . Prominent examples are solar reforming of biopolymers and nonrecyclable plastics [30–33] . Conductive polymers are a versatile platform for designing smart materials as the electrical conductivity of the polymer follows a multitude of external physical stimuli that naturally finds application in sensing [34–37] .…”
Section: Introductionmentioning
confidence: 99%
“…[29] Prominent examples are solar reforming of biopolymers and nonrecyclable plastics. [30][31][32][33] Conductive polymers are av ersatile platform for designing smart materials as the electrical conductivity of the polymer follows am ultitude of external physical stimuli that naturally finds application in sensing. [34][35][36][37] Owing to its nontoxicity, [38] flexibility,w ater-solubility,p rocessability,a nd commercial availability,p-type conductive poly(3,4-ethylenedioxythiophene) polystyrene sulfonate (PEDOT:PSS) is of great interest in the construction of functional composites and devices.I na ddition, 3D printing of PEDOT:PSS facilitates development of complex conductive patterns.…”
Section: Introductionmentioning
confidence: 99%
“…Der Gebrauch von Polymeren als Substrate fĂŒr photokatalytische Umwandlungen ist deutlich weniger erforscht [29] . Prominente Beispiele sind die solare Reformierung von Biopolymeren und nicht recycelbaren Kunststoffen [30–33] . LeitfĂ€hige Polymere bieten eine vielseitige Plattform fĂŒr das Design von intelligenten Materialien, da die elektrische LeitfĂ€higkeit des Polymers einer Vielzahl von externen physikalischen Reizen folgt, was oft Anwendung in der Sensorik findet [34–37] .…”
Section: Introductionunclassified